THE IMPACT OF ELECTRONIC PROCUREMENT ON FLEET MANAGEMENT - ADRILI JOY (My University, 2024)
The study investigated the impact of electronic procurement on fleet management at National Medical stores. It specifically; examined the effect of Electronic Procurement on Fleet Management at National Medical Stores to find out the challenges that affect the implementation of Electronic Procurement on Fleet Management at National Medical Stores and to determine the relationship between Electronic Procurement and Fleet Management at National Medical Stores. Utilizing a cross-sectional strategy, the researcher collected data using both qualitative and quantitative methods. There were 100 respondents in the study's target population, and 80 respondents were chosen at random to make up the sample size. The Krejuice Morgan table from 1970 was used to determine the sample size. Techniques for both non-purposive and purposeful sampling were used to choose the sample. The primary sources of data that were investigated were primary and secondary sources. Data were collected from journals, articles, textbooks, periodicals, and research publications, among other sources. The Questionnaire was used as data collection instruments for the study. The researcher went on to analyze data using SPSS to formulate frequency tables and charts on which data was presented. The findings in objective one revealed that electronic procurement has facilitated collaboration broad array of critical customer interactions in the organization as supported by 70% of the respondents with a mean score of 4.01.The findings in objective two summarized that propensity to adopt e-procurement has been hindered by the cost of investing in compatible systems. This generated an acceptance of 63% and a mean score of 3.37. It was finally concluded that that propensity to adopt eprocurement has been hindered by the cost of investing in compatible systems. The study further concluded that that Electronic procurement has helped in coordinating the activities to manage the supply chain management in the procurement department by early planning of the organizations procurements. It was recommended that National Medical Stores should effectively design measures on how they can cope up and mange electronic procurement systems for ease access to medical supplies, equipment and related items. It was emphasized that the government of Uganda through the Ministry of Finance and Ministry of Health should ensure that the electronic procurement is adopted to avoid problems associated with longer lead times and poor services delivery by incapable suppliers. The researcher emphasized that Universities should organize workshops and train upcoming procurement officers on the best ways to handle their electronic procurement to increase on value for money of all procurements handled in their entities of work.